1957
DOI: 10.1139/o57-096
|View full text |Cite
|
Sign up to set email alerts
|

THE DISTRIBUTION OF RADIOACTIVE CARBON IN THE RAT AFTER THE ADMINISTRATION OF RANDOMLY LABELLED C14-β-CAROTENE

Abstract: The distribution of C14 has been studied in rats following the oral administration of C14-β-carotene, which is known to be readily converted to vitamin A in the intestine. The rats were maintained in a respiration chamber and individuals removed at various time intervals up to 28 hours after dosing, and the concentration of C14 in tissues was determined. The counts per million per gram of tissue was higher in the adrenal glands and hypophysis than in the other organs examined. The pattern of C14 distribution i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1961
1961
1978
1978

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Plasma 14 contained 20% of the recovered C 17 minutes after injection but only 1-4% of the radioactivity after longer time intervals indicating that plasma does not serve as a reservoir for 14 deposition of vitamin A. Willmer and Laughland (1957) fed C-3-carotene to vitamin A-deficient rats and found after various time intervals that the total radioactivity recovered was greatest in the liver followed by the intestines, adrenal glands, blood, kidneys, lungs, heart, hypophysis, stomach and spleen. With the exception of blood and the retina, vitamin A in the body exists mainly in its esterified form (Moore, 1957) and predominately as palmitate .…”
Section: Mechanismmentioning
confidence: 99%
“…Plasma 14 contained 20% of the recovered C 17 minutes after injection but only 1-4% of the radioactivity after longer time intervals indicating that plasma does not serve as a reservoir for 14 deposition of vitamin A. Willmer and Laughland (1957) fed C-3-carotene to vitamin A-deficient rats and found after various time intervals that the total radioactivity recovered was greatest in the liver followed by the intestines, adrenal glands, blood, kidneys, lungs, heart, hypophysis, stomach and spleen. With the exception of blood and the retina, vitamin A in the body exists mainly in its esterified form (Moore, 1957) and predominately as palmitate .…”
Section: Mechanismmentioning
confidence: 99%
“…Later it was found that this compound hampered the accurate determination of these samples by radioassay methods. Willmer and Laughland (1957) overcame this difficulty. Following saponification of the plant tissue, they extracted the unsaponifiable fraction and cooled it by passing it through dry ice to remove sterols.…”
Section: Extraction Proceduresmentioning
confidence: 99%
“…Whereas diethyl ether was employed for extraction purposes in the study of Willmer and Laughland (1957), Lilly et al…”
Section: Extraction Proceduresmentioning
confidence: 99%
See 2 more Smart Citations